Test of cure study: a feasibility study to estimate the time to test of cure (TOC) for Neisseria gonorrhoeae and Chlamydia trachomatis infections. (23rd May 2020) - Sultan, Binta; Benn, Paul; Schembri, Gabriel; Patel, Hemanti; Brima, Nataliya; Alexander, Sarah; Ison, Catherine A
Abstract : Objectives: Test of cure (TOC) for Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) infection is an important tool in the public health management of STIs. However, there are limited data about the optimal time to perform TOC using nucleic acid amplification tests (NAATs) for NG and CT infections. A study was performed to assess the feasibility of a larger study to determine the optimal time to TOC using NAATS. Methods: The Sexually Transmitted Bacteria Reference Unit at Public Health England undertook testing of gonococcal and chlamydial nucleic acids within neat urine stored in different conditions over 25 days to provide evidence of the stability of the nucleic acid prior to recruitment. Individuals diagnosed with uncomplicated NG or CT infection were recruited from three sexual health clinics. Individuals were asked to return nine self-taken samples from the site of infection over a course of 35 days. Survival analyses of time to first negative NAAT result for NG and CT infection and univariate regression analysis of factors that affect time to clearance were undertaken. Results: At room temperature, chlamydial DNA in urine is stable for up to 3 weeks and gonococcal DNA for up to 11 days. We analysed data for 147 infections (81 NG and 66 CT). The median time to clearance of infection was 4 days (IQR 2–10 days) for NG infection and 10 days (IQR 7–14 days) for CT infection. Vaginal CT infections took longer to clear (p=0.031). NG infection in men who have sex with men took longer to clear (p=0.052). Conclusion: Chlamydial and gonococcal nucleic acids are stable in urine before addition of preservatives, longer than recommended by the manufacturer. The TOC results suggest that it may be possible to undertake TOC for NG and CT infections earlier than current guidelines suggest and that anatomical site of infection may affect time to clearance of infection.